Behaviour of composite slab using finite element analysis - Muhamad Dhanuri, Mat Noradin (2019)
This study present nonlinear finite element (FE) analysis of steel-concrete composite slab with profile deck subjected to four-point bending test. The aim of this study is to investigate the behavior of composite slabs strengthened with C-channels where the C-channels are bolted to the ribs of profiled steel deck. The purpose of this strengthening is to increase the flexural capacity of the composite slabs. This strengthening allows the composite slabs to constructed using unpropped construction method instead of propped construction, which is the most common method used in construction. This unpropped construction method could accelerate the construction phase as less time is needed to prepare and assemble the props. In this study, the modelling technique used to develop the FE models in present study was verified against disparate experimental test results where the result agrees reasonable well. According to the verified modelling technique, six composite slabs comprises of three unstrengthen composite slabs and three strengthened with different length were developed. All six slabs tested using FE analysis and compared the result the strengthened and unstrengthen composite slab. The result shows the strengthened composite slab have higher maximum load compare unstrengthen composite slab. The conclusion is strengthened composite slab can carry higher load capacity compare to unstrengthen composite slab.